Comparative study of anti-SARS-CoV-2 receptor-binding domain total antibody titer before and after heterologous booster with mRNA-based COVID-19 vaccine - Kamil, Qatrunnada; Putri, Widia; Ayulinda, Arianisah P.; Maelani, Imelda; Anwar, Samsul; Ichsan, Ichsan; Pranata, Agung; Mudatsir, Mudatsir; Syukri, Maimun; Rizal, Samsul; Kurniawan, Rudi; Sofyan, Sarwo E.; Harapan, Harapan (Narra Sains Indonesia, 2024)
The waning immunity following the COVID-19 vaccination become a significant concern and the immunological dynamics of vaccine-induced antibodies after vaccination need to be explored. The aim of this study was to compare anti-SARS-CoV-2 receptor-binding domain (RBD) antibody levels before and after a booster dose with heterologous COVID-19 vaccine and to identify factors influencing the levels after receiving the booster dose. A cross-sectional study was conducted in which individuals who received primary doses of CoronaVac and a booster dose with an mRNA-based vaccine were recruited using a purposive sampling technique. The titers of anti-SARS-CoV-2 RBD antibodies were measured using an enzyme-linked immunosorbent assay (ELISA), and plausible associated factors were collected using a questionnaire-assisted face-to-face interview. The Wilcoxon test was used to compare the titers before and after the booster dose, while the Kruskal-Wallis and Mann-Whitney tests, followed by multivariate linear regression, were used to assess the factors associated with RBD total antibody titers. The results showed that there was a significant increase of anti-SARS-CoV-2 RBD total antibody titers before and after receiving the booster dose (1,558.7 BAU/mL vs 140.6 BAU/mL, p<0.001). The analysis revealed that age (p=0.555), sex (p=0.254), type of vaccine (p=0.914), presence of hypertension (p=0.541), diabetes (p=0.975), chronic obstructive pulmonary disease (COPD, p=0.620), and gout (p=0.364) were not associated with anti-SARS-CoV-2 RBD total antibody titers. However, the titers of anti-SARS-CoV-2 RBD total antibody were significantly different between those with and without hyperlipidemia (p=0.021). This study suggests that a booster dose with a heterologous COVID-19 vaccine could significantly enhance immune responses against COVID-19, and therefore, this strategy may be recommended as part of preventive measures to strengthen immunity against COVID-19.